Designing and developing the strategic system of wrestling in I.R. Iran improving wrestling in Islamic Republic of Iran - Goudarzi, M.; Honari, H. (World Journal of Sport Sciences, 2009)
Improving wrestling in Islamic Republic of Iran depends on a long-term vision, which emphasizes on the necessity to have strategic plans and long-term planning. In general, this plan should be developed due to the weaknesses and strengths of wrestling in Iran and it should be specified by the abilities of federation and wrestling associations of different provinces in the country. On the other hand, the possible threats and opportunities to achieve the objectives of an ideal vision are important in developing this plan, which notifies the desirable strategies and policies according to the ingredients of strategic plan and also investing sufficient attention in wrestling in developed countries. The main objective of this research is to develop an ideal strategic plan for wrestling in Iran with executing comparative studies, analyzing the weaknesses and strengths and eventually developing strategies and the mission. For collecting the necessary data, 65 experts among the sport managers university professors and executive staff were selected (age 50.6±3.6, years of experience 24.6±2.8). For comparative studies, the required data were collected from six countries including Germany, United States of America, Japan, Turkey, Canada and United Kingdom and also the International Wrestling Federation (FILA). For data analysis, SWOT method and a 4x4 matrix were used. In each square of the matrix, one of the effective aspects was applied in the system and it was finally verified and compared with other aspects. The mentioned aspects were human resources, financial resources, technology and information, in which the weaknesses, strengths and opportunities for the organization were evaluated, the threats were notified in external and internal dimensions and assessed inside and outside the organization. After detecting the quadripartite aspects, the Freeman statistical method was used to choose the priorities in each matrix. The existence of scientific programs, modern and developed facilities in rival countries and sufficient credits were determined as the threats. Organizing regular competitions among clubs and universities and governmental organizational supports were determined as the opportunities for developing wrestling in Iran. The verified internal weaknesses were the lack of qualified managers in wrestling associations of provinces, shortage of complied and classified programs, paying less attention to the scientific principles in training and educating wrestlers and finally look for merited and qualified coaches. Determining and identifying the internal and external aspects and other effective components in wrestling was the main purpose of this research; and the findings of this study could be useful planning with positive effects.